Tidsstudier i kalvuppfödning - Lilja Johansson, Marjo (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
Swedish agriculture stands in front of big changes the whole time. As a milking producer you have to adapt and develop the company to these changes and find the best solution. This potential is easy to find if you compare your company with other similar companies. Labour cost is the biggest cost in milking production after the cost for food. Today it is rather easy to measure how many hours per cow different system of cow houses needs, but we do not know so much about how many hours it takes to breed a calf. To learn more about the labour time with the calves during the first time after the calf was born, I made time studies on five different farms with calf hutches, automatic milk system, large calf boxes, and smaller calf boxes with teat buckets. The farmers had between 150 and 300 cows. The farmers studied the labour time they needed with their calves and registered 17 different parts during 14 days. The different data was put together in five points and the different systems were compared with each other and the result was presented as time per calf and day and the total time the farmer gave milk to the calf. It is very important to have a system easy to care for during the whole milk period. The calves have to grow well and keep themselves healthy, because if you keep your calves healthy, you save a lot of working time too. You have to keep the calves in a homogeneous, gathered system near the barn, so the probation and care of the calves will become easy and rational. You should rather not move the calves inside the system during the milk period. It must be easy to get litter, food and other things that are necessary and some times it is easier to make a warehouse near the calves instead of transport every day from a place far away. It is also important that you have calf births at regular intervals during the whole year and try to do much of the work with machines instead of using manual labour. My study showed that calf hutches had the lowest time per calf. There were two systems of calf hutches, with concrete board as a floor in the calf hutches and the other system with the hutches standing on gravel. The farm with calf hutches on a concrete board used 2, 24 minutes per calf and totally 157 minutes during the whole milk period per calf. The other farm with calf hutches standing on gravel used 2, 38 minutes per calf and totally 167 minutes during the whole milk period per calf. The highest labour time per calf had the farm with two systems for their calves. They had calf hutches and small boxes with buckets for each calf. They used 6, 77 minutes per calf with their calf hutches and totally 406 minutes during the whole milk period per calf. The other system on this farm was small calf boxes with a teat bucket for each one of the calves. They used 6, 51 minutes per calf in this system and totally 390 minutes during the whole milk period per calf. The result on this farm was treated unfairly a little bit, because there was so low number of calves at the moment.